The Annals of the Parish: Referendum Year 2014. Issue 1 (February 2015) - Bort, Eberhard
<x xml:space="preserve">Abstract</x> The decisive No vote in the Scottish independence referendum on 18 September 2014 was not a vote for the constitutional status quo, although it confirmed that Scotland would remain part of the United Kingdom. The referendum outcome is likely to have far-reaching consequences for the power relations between London and Edinburgh and, perhaps more than expected, for the constitutional future of the entire UK. A tight timetable for the delivery of extra powers for the Scottish Parliament is in place, and the 'elephant in the room', the constitutional status and governance of England, is now firmly on the agenda. There is also pressure for decentralisation in Scotland itself. And the huge 'democratic awakening' which characterised this 'national conversation' about Scotland's future, with massive democratic participation and a record turnout, demands that these changes will have to be brought about in a participative way – and not 'top-down', as a Westminster or Holyrood 'stitch-up'.